1993
DOI: 10.1007/bf02072519
|View full text |Cite
|
Sign up to set email alerts
|

Family investigations in idiopathic hypercalciuria

Abstract: We analysed some genetic and environmental factors influencing renal (RH) and absorptive hypercalciuria (AH) the main subtypes of idiopathic hypercalciuria (IH). Their distinction is essential in the prevention and treatment of urolithiasis. Twenty-one children admitted for renal stones had IH (8 RH and 13 AH). Their families were investigated with the participation of a total of 68 family members including 62 first-degree relatives. They were all normocalcaemic. Their urinary calcium excretion was measured on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Insufficient nutrient, and especially Ca, intake also resulted in very low values of calciuria (0.18 mg/kg per day) in Ugandan boys and girls [37]. Lower mean calciuria values than in the recent study have also been observed, e.g., under special physiological conditions, such as in children with low Ca and low sodium intake (1.54 mg/kg per day) [34] or pathological conditions, such as in children with acute airway infections (1.28 mg/kg per day) [38].…”
Section: Discussionmentioning
confidence: 49%
“…Insufficient nutrient, and especially Ca, intake also resulted in very low values of calciuria (0.18 mg/kg per day) in Ugandan boys and girls [37]. Lower mean calciuria values than in the recent study have also been observed, e.g., under special physiological conditions, such as in children with low Ca and low sodium intake (1.54 mg/kg per day) [34] or pathological conditions, such as in children with acute airway infections (1.28 mg/kg per day) [38].…”
Section: Discussionmentioning
confidence: 49%
“…Pak et al, in four generations of a family with absorptive hypercalciuria [19], observed an autosomal dominant pattern. Harangi and Mehes suggested that renal hypercalciuria is inherited as an autosomal dominant trait, while absorptive hypercalciuria is more likely to have dietary causes [13]. Nicolaidou et al studied 40 children with hypercalciuria and found that 47.5% of them had at least one hypercalciuric first-degree relative, while 52.5% were sporadic cases due possibly to a de novo mutation or other causes [12].…”
mentioning
confidence: 97%
“…(2) In children with fasting hypercalciuria the lack of an increase in bone turnover implies that renal and absorptive hypercalciuria may not be two distinct entities [11]. (3) In studies on families of children with hypercalciuria, Nicolaidou et al [12] and Harangi and Mehes [13] found that renal and absorptive hypercalciuria may coexist in the same family, an argument in favor of a single form of idiopathic hypercalciuria. Lerolle [16]: if it is normal, administration of the vitamin increases intestinal calcium absorption and produces an increase in urinary calcium excretion (absorptive hypercalciuria); if calcium intake is restricted, however, calcitriol administration leads to increased bone turnover and higher urinary calcium levels (resorptive hypercalciuria).…”
mentioning
confidence: 98%
“…Some investigators were unable to find distinct differences; others detected renal and absorptive hypercalciuria in the same patients when examined at different points of time [5]. Furthermore, the concerns about this test were supported by the findings in familial forms of IHC where different subtypes were found within the same family [13], and finally, the question has been brought up if renal and absorptive hypercalciuria may just represent the two ends of one broad spectrum [6]. …”
Section: Discussionmentioning
confidence: 97%